Service, satisfaction, and climate perspectives on management in English language teaching - Walker, John. (Bingley, U.K. : Emerald, 2010)
Customer Service and Climate in English Language Teaching presents the results of research carried out in New Zealand to demonstrate the ways ELT can be conceptualized in terms of service and climate. Although ESL is a major worldwide service industry employing large numbers of professionals and serving millions of clients, it is an under-researched field and one that is under-represented in the management/business literature. This omission is particularly noticeable, given that ELT has its own particular themes, problems, and issues. For instance, ELT is an educational service, yet exists within a commercial context. Its clients are from different cultural and linguistic backgrounds. In many ELT contexts, the cultural and linguistic backgrounds of the service providers are different from those of the clients. Thus, the service provision has a strong cross-cultural dimension. Yet the ELT sector is largely missing from the educational and the management literature. This book seeks to fill the gap through discussion of ELT as a service, issues surrounding ELT teachers as service providers, the work of ELT managers, client expectations and perceptions of ELT service, comparison of staff estimates and client ratings of service quality, and considerations of service milieu and climate in ELT centers.
ch. 1. ELT as a service / John Walker -- ch. 2. ELT service and student satisfaction / John Walker -- ch. 3. Service climate in ELT / John Walker -- ch. 4. Student views of ELT service / John Walker -- ch. 5. Student satisfaction with English language teaching center service / John Walker -- ch. 6. Staff perceptions of the service dimension in ELT / John Walker -- ch. 7. Service climate in English language teaching centers : a surveying of providers / John Walker -- ch. 8. Are they as satisfied as we think they are? : comparing staff and student perceptions of ELTC service quality / John Walker -- ch. 9. Finding an identity : the tertiary manager's view of ELT work / John Walker -- ch. 10. Service operation applications in ELT / John Walker -- ch. 11. Researching ELT management / John Walker -- ch. 12. Issues and implications for ELT managers / John Walker.
Includes bibliographical references.
Keywords: English language -- Study and teaching -- Foreign speakers; Language schools -- New Zealand -- Administration